2013
DOI: 10.1590/1516-4446-2013-s108
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric anxiety disorders: from neuroscience to evidence-based clinical practice

Abstract: The objective of this narrative review of the literature is to describe the epidemiology, etiology, pathophysiology, diagnosis, and treatment of pediatric anxiety disorders. We aim to guide clinicians in understanding the biology of anxiety disorders and to provide general guidelines for the proper diagnoses and treatment of these conditions early in life. Anxiety disorders are prevalent, associated with a number of negative life outcomes, and currently under-recognized and under-treated. The etiology involves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 188 publications
(189 reference statements)
0
24
0
6
Order By: Relevance
“…31,32 The fear system matures in the beginning of infant development; as a consequence, normative fears are commonly present since very early in life. 5,33,34 Our data showed that common fears occur in Rev Bras Psiquiatr. 2017;39 (2) Specific and social fears in children most children and adolescents, and it is their intensity that differentiates normative from clinically salient manifestations.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…31,32 The fear system matures in the beginning of infant development; as a consequence, normative fears are commonly present since very early in life. 5,33,34 Our data showed that common fears occur in Rev Bras Psiquiatr. 2017;39 (2) Specific and social fears in children most children and adolescents, and it is their intensity that differentiates normative from clinically salient manifestations.…”
Section: Discussionmentioning
confidence: 68%
“…3,4 In contrast, clinically significant specific phobias and social phobias are characterized by one or more persistent fears that cause distress and impairment to the child's life. 1,5 The prevalence of specific and social phobia in children and adolescents is 2.9 and 0.3% respectively. 6 In short, the presence of fears is typically normative, and only a minority of children is significantly impaired by fears requiring clinical attention.…”
Section: Introductionmentioning
confidence: 99%
“…This can become one of the most overwhelming challenges to the child's basic trust during their natural development. Such anxiety usually resolves spontaneously through carers' support and more and better social awareness [237][238][239]. Unresolved physiological separation anxiety can contribute to the development of complications including pathological separation anxiety, social anxiety, and school phobia [240].…”
Section: Physiological Social Anxietiesmentioning
confidence: 99%
“…1 Most adults with AD report that their anxious symptoms had onset early in life, especially during childhood and adolescence. 2,3 According to epidemiological data from multiple sources, the prevalence of AD ranges from 3.1 to 17.5% in children and adolescents, 4 while the current global prevalence is 7.3%.…”
Section: Introductionmentioning
confidence: 99%